Prosódia semântica do item lexical mulher em letras de música brasileira : contribuições da linguística de córpus - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
This master's research assumes that portuguese language song lyrics can be a resource for teaching, considering their lexical repertoire and how easily they can be accessed by students. Given the need to problematize the treatment of women in society in the classroom while promoting lexico-cultural education in basic education, this research aims to identify, in the lyrics of different Portuguese-language musical styles, the semantic prosody relative to the lexical field "woman", taking into account cultural studies focused on the cultural baggage shared by words. As for specific objectives, the study aims to: 1) survey the mentioned lexical item and its variants, as well as the lexical horizon; 2) verify, within the scope of the 05 most popular musical styles in Brazil, the semantic prosody related to women; 3) establish a connection between educational documents and cultural studies; and 4) develop and present a proposal for a didactic sequence for the implementation of educational guidelines and gender awareness. The theoretical and methodological foundation is anchored in the studies of Lexiculure (BARBOSA, 2009; KRAMSCH, 2013) and Corpus Linguistics (BERBER SARDINHA, 2004, 2009, 2012; BIBER, CONRAD; REPPEN, 2004). Regarding the material and method, a corpus of Portuguese-language song lyrics was compiled from the Vagalume website, comprising 43 styles, 1,191 artists, 69,621 lyrics, and 12,709,768 words. The results indicate different perspectives on the treatment of women, ranging from objectification to idealization, which demands discussion and awareness-raising in the Portuguese language classroom. The contribution of the research lies in lexico-cultural education, bringing reflections on lexical repertoire and its intercultural representativeness to the classroom, culminating in proposals to combat gender inequality. In addition, the study also served to put on the agenda inconsistencies between the discourse adopted by us, women, when questioning, positioning ourselves against sexist behaviors, but at least we act, even if without realizing it, as replicators of it through our lexical choices in our daily lives. Thus, our research has brought to light how this behavior is ingrained in our culture through words, expressions, popular sayings, which reveal a derogatory thought towards women, which comes not only from men, but also from women.
Semantic prosody of the lexical item woman in b razilian music lyrics : contributions of corpus linguistics
Keywords: Lexicultura; Prosódia semântica; Mulher; Lexiculture; Semantic prosody; Woman; LINGUISTICA, LETRAS E ARTES::LINGUISTICA